Guide to ship repair estimates (in man-hours) - Butler, Don
Don Butler has compiled an invaluable list of the man-hours required for ship repair estimates. All ships must undergo regular dry-docking for examination by a third party surveyor; this is a mandatory requirement for ships which ply their trade on either world wide or coastal area basis. This dry-docking period is usually used as a time to carry out known damage repairs, cleaning and painting, upgrades and regular machinery overhauls. The author provides estimates for all situations which may arise, enabling the repair superintendent to anticipate costs, and therefore to prepare an accurate repair specification well in advance, for issue to the repairer. Don Butler has gathered the information in this book over more than twenty years in the repair field. He is a holder of the DTI Combined first class Engineers Certificate of competency for steam and motor ships and a Fellow of the Institute of Marine Engineers (F.I.Mar.E). He is also a Member of the Society of Consulting Marine Engineers and Ship Surveyors (M.C.M.S). Produced for technical superintendents of ship owners and ship managers; outlines the manner in which ship repair companies compile quotations. Made up of man-hours rather than monetary value, to assist long-term pricing; books of 'prices only' will have no long-term relevance, whereas time in man-hours will be universally applicable and more durable.